Effect of polythene-covering on above-ground tuberization and storage roots yield in cassava (Manihot esculenta Crantz) - Abdullahi, N.; Bujang, Japar Sidik; Ahmed, Osumanu Haruna; Zakaria @ Ya, Muta Harah (Horizon Publisher, 2014)
Present study aimed to investigate the effectiveness of polythene-covering on activation of dormant auxiliary buds on the stem for lateral tuber formation and the resultant effect on total storage roots yield. Three time intervals i.e. 1 day after planting, 30 days after planting and 60 days after planting used as treatment, and uncovered stem used as control. Treatments were tested in randomized complete block design with three replications. Regardless of the variety, stem polythene-covering at day 1 after planting showed the highest effect with respect to storage roots production and yield components tested. However, the effect of stem polythene-covering at day 1 after planting in terms of dry mass partitioning to storage roots was the lowest across all the treatments (25.50 to 27.37% of the biomass) compared to that of stem covering at day 60 after planting (33.10 to 37.20%). This study opens new perspectives in cassava yield improvement which hitherto has not been exploited.